2021
DOI: 10.1002/ldr.3955
|View full text |Cite
|
Sign up to set email alerts
|

The role of root‐associated microbes in growth stimulation of plants under saline conditions

Abstract: Soil salinization has adverse effects on plant growth due to direct ion toxicity or secondary damage, such as mineral nutrition imbalance and the water stress caused by low osmotic potential. The rhizosphere processes of plants are likely to play an important role in the biological improvement of saline soil. However, the understanding of this remains limited. This review summarizes the progress made recently in exploring the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 124 publications
(119 reference statements)
0
23
0
Order By: Relevance
“…Many saline-alkali resistance microorganisms [ 23 ] not only reduced soil salinity [ 24 ], but also had the functions of nitrogen fixation [ 25 , 26 ], potassium [ 27 ] and phosphate solubilization [ 10 , 28 ]. Because of their functions, these microorganisms have great application potential on improving the nutrition of saline-alkali soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many saline-alkali resistance microorganisms [ 23 ] not only reduced soil salinity [ 24 ], but also had the functions of nitrogen fixation [ 25 , 26 ], potassium [ 27 ] and phosphate solubilization [ 10 , 28 ]. Because of their functions, these microorganisms have great application potential on improving the nutrition of saline-alkali soil.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their functions, these microorganisms have great application potential on improving the nutrition of saline-alkali soil. Thus, these microorganisms may be used to improve saline-alkali soil [ 10 , 23 , 24 ]. Moreover, many microorganisms secrete bioactive substances such as IAA [ 28 30 ], ACC deaminase [ 31 , 32 ], gibberellin [ 30 ], exopolysaccharides [ 33 , 34 ] and polyamine [ 35 ] etc., which activate the antioxidant system of plants and promote plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies showed that seed treatment with T. longibrachiatum T6 promoted seed germination and increased the shoot and root weights of wheat under salt-stress conditions . Beneficial soil microorganisms have demonstrated extensive potential for crop improvement under saline conditions . Besides, they can also promote the growth of wheat under nonsaline conditions. Application of T. longibrachiatum T6 can lead to changes of some indicators related to improving salt tolerance in wheat under nonsaline conditions, including the increase of the content of chlorophyll, proline, ascorbate, glutathione, reducing the content of malondialdehyde (MDA), and promoting the expression of antioxidant enzyme genes ( SOD , POD , and CAT ). , However, it needs to be verified whether this promoting effect of T. longibrachiatum T6 on salt tolerance is direct or indirect.…”
Section: Conventional Approaches To Enhance Salt Tolerance In Wheatmentioning
confidence: 99%
“…Phytoremediation efficiency is strongly dependent on the nature of root secretions, because root secretions, including hydrogen ions, organic acid anions, phytochelators, enzymes, and carboncontaining metabolites, which can promote complex formation and reduce heavy metal toxicity through chelation or hydrogen bonding (Yang et al, 2020). These roots secretions also attract beneficial rhizosphere growth-promoting bacteria, which facilitate plant growth under stress (Liu et al, 2021).…”
Section: Role Of Plant Biomass and Roots In Phytoremediationmentioning
confidence: 99%